Psychological and Structural Barriers to Immigrant Community Participation: The Experience of Peruvians in Santiago de Chile. Issue 3 (30th October 2020) - Martinez Damia, S.; Marzana, D.; Alfieri, S.; Pozzi, M.; Marta, E.; Martinez, M.L.
Abstract: Community participation can be considered a pillar for the promotion of social justice and well‐being for immigrants in new countries. Participation may be influenced by different forms of oppression which decrease opportunities for immigrants to be engaged. The present study explores the difficulties that Peruvian immigrants encountered and still encountering to participate in Santiago de Chile through in‐depth qualitative interviews. Eighteen semi‐structured interviews were conducted with Peruvian leaders of Ethnic Community Based Organizations (ECBOs) in Santiago de Chile. Interviews focused on the community engagement of Peruvians highlighting the difficulties they encountered when deciding whether to engage and throughout the process of carrying out their commitment, along with their perceptions when trying to engage their compatriots. The present study contributes to the literature in three aspects. First, it focused on the phenomenon of South–South migration. Secondly, it delved into the psychological and structural barriers that immigrants' experience, considering their disadvantaged conditions. Thirdly, it used Situational Analysis, along with the constructionist drift of Grounded Theory, which is widely used in critical, qualitative research, and is sensitive to producing situated knowledge. Coding and mapping analysis identified experiences related to historical trauma, transnational bonds, and dominant master narratives in both countries as well as challenges due to balancing time and priorities, surviving institutional deterrents, and inter‐organizations competitiveness. Finally, transnational commitments, mechanisms of social disconnection, and under valuated rights that Peruvians may live in Chile were pointed out. These results intend to have practical implications for immigrants and for community psychologists. Highlights: Community participation of immigrants is a pillar for the promotion of social justice. Psychological and structural barriers to community participation of immigrants must be detected. Barriers can be related to historical and transnational connections of immigrants. Barriers can be related to the difficulties of continuing with a community‐based organization. Barriers can be related to the psychological empowerment of immigrants.